Methane decomposition over Fe-based catalysts - Karaismailoglu, Meltem; Figen, Halit Eren; Baykara, Sema Z. (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
Catalytic approach for methane decomposition can be seriously considered as a promising process for COx free hydrogen generation. In this study, catalytic methane decomposition was performed using Fe-based catalysts, and catalytic performance tests were carried out in a CH4:N-2 flow at 750 and 800 degrees C. The analyses of reaction products were carried out by a mass spectrometer. For the preparation of Fe-based catalysts, sol-gel method was utilized. Yttria (Y2O3) and alumina (Al2O3) were used as support materials. Theoretical molar ratios (Fe2O3/Y2O3/Al2O3) of the samples C1-C5 were 1:0:0, 1:1:0, 1:1:5, 2:1:4 and 3:1:6, respectively. The characterization analyses of fresh and spent catalysts were performed with XRD, SEM, TPR, TG-FTIR and BET surface analysis techniques. Surface basicity of catalysts was determined via CO2-TPD measurements. In the presence of Fe2O3/Y2O3 and Fe2O3/Y2O3/Al2O3 catalysts, methane conversions of 29% and 4% were achieved at 750 degrees C. Adding alumina into Fe2O3/Y2O3 catalyst leads to the formation of garnet type crystal structure which reduces catalytic activity. (C) 2020 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Catalytic methane decomposition; Hydrogen; Fe-based catalyst; HYDROGEN-PRODUCTION; CARBON NANOTUBES; IRON CATALYSTS; REDUCTION; Chemistry; Electrochemistry; Energy & Fuels